Effects of GV14 Acupuncture on Cerebral Blood Flow Velocity in the Basilar and Middle Cerebral Arteries and CO2 Reactivity during Hypercapnia in Normal Individuals. (9th September 2021) - Lee, Hyun Ku; Moon, Sang-Kwan; Jin, Chul; Cho, Seung-Yeon; Park, Seong-Uk; Jung, Woo-Sang; Park, Jung-Mi; Ko, Chang-Nam; Cho, Ki-Ho; Kwon, Seungwon
Abstract : The Governing Vessel 14 (GV14) (Dazhui) is one of the acupuncture points referred to as "seven acupoints for stroke." Nevertheless, there is a scarcity of research on the effects of acupuncture treatment at GV14. This study investigated the effects of acupuncture at GV14 on cerebral blood flow (CBF), especially that in the basilar artery (BA) and the middle cerebral arteries (MCA). Sixteen healthy men aged 20 to 29 years were enrolled in this study. CBF velocity and cerebrovascular reactivity (CVR) were measured using transcranial Doppler sonography (TCD). The following were assessed: closed circuit rebreathing- (CCR-) induced carbon dioxide (CO2 ) reactivity, modified blood flow velocity at 40 mmHg (CV40) on BA and MCAs, blood pressure (BP), and heart rate (HR). Observed results were obtained after comparison with the baseline evaluation. Statistically significant elevations in CO2 reactivity were recorded in the BA (3.28 to 4.70, p < 0.001 ) and MCAs (right: 3.81 to 5.25, p = 0.001 ; left: 3.84 to 5.12, p = 0.005 ) after acupuncture at GV14. The CV40 increased statistically significantly only in the BA (45.49 to 50.41, p = 0.003 ). No change was observed in BP (106.83 to 107.08 (mmHg), p = 0.335 ) and HR (77 to 75 (bpm), p = 0.431 ). Acupuncture at GV14 improved CBF velocity. These results could be explained by the regulation of endothelium-dependent vessel dilation effected by acupuncture. This trial is registered with Korean Clinical Trial Registry (http://cris.nih.go.kr ; registration number: KCT0004787).